A case study of the goals of the business communication course at Technikon Witwatersrand - Vongo, Mthuthuzeli Rubin (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2006)
At Technikon Witwatersrand, Business Communication is offered as a service subject, which is compulsory for a variety of diplomas and the majority of students are obligated to do the course. Its broad intention is to assist students in developing their proficiency in English, enabling them to cope with studying at Technikon and preparing them for the workplace. Despite the fact that the course is designed to assist them, many students question why they have to do the course and whether it is simply a repetition of high school work. The study attempts to examine the implicit and explicit goals of Business Communication, to explore the process through which the goals have been developed and changed over the years (i.e. how the goals have been constructed), and to elicit and compare the perspectives of the different stakeholder groups as to the goals. Both a qualitative and a quantitative approach are used in the research design. Interviews with four fulltime lecturers were conducted and a self-designed questionnaire was administered to students. These were the main means of data collection. The data reveals that the goals of Business Communication are implied rather than explicit. Despite this, students and lecturers see the course as important. Recommendations are made to help the Department of Business Communication to reflect on their practice with particular emphasis given to material development and the application of OBE principles.
Keywords: Communication in education -- South Africa; Communication -- Study and teaching (Higher) -- South Africa; English language -- Study and teaching (Higher) -- South Africa; Curriculum change -- South Africa; Competency-based education -- South Africa